2016
DOI: 10.1038/srep21901
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal co-ordination of RhoA, Rac1 and Cdc42 activation during prototypical edge protrusion and retraction dynamics

Abstract: The three canonical Rho GTPases RhoA, Rac1 and Cdc42 co-ordinate cytoskeletal dynamics. Recent studies indicate that all three Rho GTPases are activated at the leading edge of motile fibroblasts, where their activity fluctuates at subminute time and micrometer length scales. Here, we use a microfluidic chip to acutely manipulate fibroblast edge dynamics by applying pulses of platelet-derived growth factor (PDGF) or the Rho kinase inhibitor Y-27632 (which lowers contractility). This induces acute and robust mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 31 publications
13
98
0
Order By: Relevance
“…We show that septins interact with microtubules via EB1, which is a multifunctional interaction partner at the microtubule tip (21)(22)(23)(24)(25). Pull-down experiments and surface plasmon resonance spectroscopy, exhibiting K d values in the nanomolar range, revealed that septins bind directly to EB1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We show that septins interact with microtubules via EB1, which is a multifunctional interaction partner at the microtubule tip (21)(22)(23)(24)(25). Pull-down experiments and surface plasmon resonance spectroscopy, exhibiting K d values in the nanomolar range, revealed that septins bind directly to EB1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the structures involved are largely enigmatic. We asked whether the plus-end tracking protein-1 (EB1), which is a master regulator of protein interactions at the plus-ends of microtubules (21)(22)(23)(24)(25), plays a role in septin-microtubule communication. In fact, GST-pull-down experiments with EB1-loaded beads revealed a direct interaction of septins with EB1.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…2D). This periodic Rac1 activation drives actin polymerization at the leading edge pushing protrusion-retraction cycles (Machacek et al, 2009;Martin et al, 2016;Pertz, 2010;Tkachenko et al, 2011).…”
Section: Analyzing the Dynamics Of The Rhoa-rac1 Interaction Networkmentioning
confidence: 99%
“…During FcγR-mediated phagocytosis, the processes of phagosome formation consisting of lamellipodial extension ( phagocytic cup formation) and phagocytic cup closure ( phagosome internalization) are highly dependent on actin assembly and remodelling (Aderem and Underhill, 1999;Araki et al, 1996Araki et al, , 2003Swanson, 2008;Swanson et al, 1999). The actin dynamics are known to be coordinated by both phosphoinositide metabolism and Rho family GTPases by which a variety of actin-binding proteins are recruited and/or activated (Beemiller et al, 2006(Beemiller et al, , 2010Caron and Hall, 1998;Chimini and Chavrier, 2000;Csépányi-Kömi et al, 2012;Martin et al, 2016;Niedergang et al, 2016). However, the precise mechanism underlying spatiotemporal regulation of phagosome formation remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%